An evaluation of screening measures for cognitive impairment after stroke - Blake, Holly; McKinney, Michelle; Treece, Karen; Lee, Elizabeth; Lincoln, Nadina (Oxford University Press, 2002)
Objectives: to assess the sensitivity and specificity of a screening battery for detecting cognitive impairment after stroke.